2016
DOI: 10.1088/1367-2630/18/4/043012
|View full text |Cite
|
Sign up to set email alerts
|

Scanning and resetting the phase of a pinned spiral wave using periodic far field pulses

Abstract: Spiral waves in cardiac tissue can pin to tissue heterogeneities and form stable pinned waves. These waves can be unpinned by electric stimuli applied close to the pinning center during the vulnerable window of the spiral. Using a phase transition curve (PTC), we quantify the response of a pinned wave in a cardiac monolayer to secondary excitations generated electric field pulses. The PTC can be used to construct a one-dimensional map that faithfully predicts the pinned wave's response to periodic field stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…(c) s < 0 for faster pacing T < T v , the scanning moves in the opposite direction. E-pulse reaches the excitable gap 'e' , excites an AP thus resetting the rotation phase, and all subsequent pulses get into the same phase [25,27]. It does not reach the VW.…”
Section: Pinned Vorticesmentioning
confidence: 99%
“…(c) s < 0 for faster pacing T < T v , the scanning moves in the opposite direction. E-pulse reaches the excitable gap 'e' , excites an AP thus resetting the rotation phase, and all subsequent pulses get into the same phase [25,27]. It does not reach the VW.…”
Section: Pinned Vorticesmentioning
confidence: 99%
“…In these papers, it was demonstrated that vortices that were assumed to be pinned at larger heterogeneities in cardiac tissue are best terminated if the pacing frequency in a LEAP procedure is set to be 80 -90% of the dominant frequency (the rotation frequency of the vortex around the pinning site). Such a choice of pacing frequency allows for an efficient scanning of the phase of the vortex in order to find the vulnerable window for vortex termination 27,28 . A simulation study in a realistic three-dimensional cardiac geometry demonstrated for selected examples that LEAP works for a pacing period of 88% of the VF cycle length, but often fails for much faster pacing with a period of 16% of the VF cycle length 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of unpinning using two-dimensional experimental and numerical models show that the UW in such cases are very narrow [16,18]. However, multiple field pulses are much more efficient in in vivo experiments.…”
Section: Discussionmentioning
confidence: 99%